Psychological Wellbeing of Diabetic Individuals, Prediabetics, and Non-diabetics: A Population-Based Study in Saudi Arabia - Aldossari, Khaled K.; Shubair, Mamdouh M.; Al-Ghamdi, Sameer H.; Alduraywish, Abdulrahman A.; Almeshari, Alhanouf Abdullah; Alrasheed, Abdullah A.; Aldahash, Raed; Angawi, Khadijah; Gaissi, Anood; Alhumud, Hana Abdullah; El-Metwally, Ashraf (Frontiers in Psychology, 2022)
Background The increased burden of diabetes affects the quality of life, including psychosocial problems. The study aims to compare the psychological well-being of individuals who are prediabetic, diabetic, or non-diabetic. Methods A cross-sectional exploratory study was conducted from January to June 2016 (n = 1,019) in Al Kharj, Saudi Arabia. After consent and questionnaires were filled out, trained staff took blood samples followed by anthropometry. Chi-squared tests, one-way ANOVA, and multiple linear regression analyses were conducted to examine the association between diabetes classes defined by HbA1c cut-off levels set by the American Diabetes Association (three categories), individual items, and total score in general health questionnaire (GHQ). An ROC curve was plotted for the total GHQ-12 score against HbA1c. Findings The mean GHQ score for psychological distress was significantly higher (F = 6.569, P = 0.038) in the diabetics (mean = 14.7) and the prediabetics (12.4) than in the non-diabetics (10.71). Four out of six positive GHQ items and three out of six negative GHQ items significantly differed among the three classes of diabetes. The adjusted multivariate analysis revealed that people with diabetes were most likely to report psychological distress compared to non-diabetics (unstandardized beta = 2.414; P = 0.037). The AUC examining the relationship between HBA1c and GHQ scores showed a moderate but statistically insignificant sensitivity/specificity of 0.643 (P = 0.23). Conclusion This study demonstrates that psychological wellbeing is substantially poorer among diabetic or prediabetic individuals than non-diabetic individuals. Future longitudinal studies are required to examine a plausible causal relationship between diabetes/prediabetes and psychological distress.